2021
DOI: 10.22306/al.v8i2.220
|View full text |Cite
|
Sign up to set email alerts
|

Rail Deliveries of Bulk Oil Cargoes From the Caspian Region to Europe

Abstract: This article is a study of the current situation with rail deliveries of bulk oil cargoes from the Caspian region to Europe. It addresses the importance of these deliveries for the European energy security, the salient features of rail transportation of crude oil and refined products in this direction, the main transportation routes, and, finally, describes existing and potential problems with rail deliveries of bulk oil cargoes from the Caspian region to Europe and suggests potential resolutions for these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some of interviewees pointed out that the passive position of shippers who are afraid to annoy the government bodies concerned and the railway administration is counterproductive. This problem was also addressed in [3]. The interviewees then indicated that the national government should understand that the danger of collapse of Kazakhstan Temir Zholy, which is not just a commercial company (though its commercial significance is enormous).…”
Section: Resultsmentioning
confidence: 99%
“…Some of interviewees pointed out that the passive position of shippers who are afraid to annoy the government bodies concerned and the railway administration is counterproductive. This problem was also addressed in [3]. The interviewees then indicated that the national government should understand that the danger of collapse of Kazakhstan Temir Zholy, which is not just a commercial company (though its commercial significance is enormous).…”
Section: Resultsmentioning
confidence: 99%
“…(ii) Supply chain resilience has been a debate for quite some time, i.e., in [10] it was underlined that "price volatility continues to provide an important incentive -for resourceimporting and -exporting countries alike -to pursue less resource-intensive economic pathways." In this regard, in [45] it was stated that "support from governments… is particularly essential". The pandemic added incentives to shift to a CE.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%